STATISTICAL APPROACH TO CHOICE OF TEMPLATES AT RECOGNITION OF THE OBJECTS GRAPHIC PRESENTATIONS - V. S. Mukha; A. N. Kuzkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The analysis of approaches to choice of templates at recognition of the graphic presentations of objects is executed. It is offered to use the statistical templates alongside with deterministic templates. Two ways of the statistical templates creation are offered. The testing of different templates and different methods of the recognition of the handwritten small letters and tree's sheets is performed. As a result the significant increasing of authenticity of recognition with statistical templates is discovered.